Distribution of HCV Genotypes Among People Who Inject Drugs in Tunisia: New Evidence for Scaling Up Prevention and Treatment Toward National Elimination Goal - Chouikha, Anissa; Ghrabi, Amine; Ghodbane, Amira; Hammemi, Walid; Khedhiri, Marwa; Sadraoui, Amel; Touzi, Henda; Hassine, Hichem Ben; Maatoug, Sonia; Bensaoud, Chaima; Abdelhak, Sonia; Bouarrouj, Samir; et al. (Frontiers in Microbiology, 2021)
Little is known about the distribution of hepatitis C virus (HCV) genotypes among people who inject drugs (PWID) in North African countries, including Tunisia. This study aims to describe HCV genotypes circulating among Tunisian PWID. A cross-sectional study was conducted, and 128 HCV-positive PWID were recruited between 2018 and 2019 from community-based harm reduction centers. After informed consent, sociodemographic characteristics and risk behavior data were obtained using an interviewer-administrated questionnaire. Blood samples were collected for further serological and molecular testing. Overall, five women and 123 men were included. The median age was 39.5 years. The majority of PWID (56.3%) had less than a secondary level of education, were single (57%), were unemployed (65.6%), were incarcerated at least once (93.0%), and had a history of residency in at least one foreign country (50.8%). During the previous 12 months, 82.0% reported having reused syringes at least once, 43.8% shared syringes at least once, while 56.2% had at least one unprotected sexual relation, and 28.1% had more than two different sexual partners. Tattooing was reported among 60.2%. All positive results for HCV-infection by rapid testing were confirmed by enzyme-linked immunosorbent assay (ELISA). HCV-RNA was detectable in 79.7%. Genotyping showed a predominance of genotype 1 (52%) followed by genotype 3 (34%) and genotype 4 (10%). Four patients (4%) had an intergenotype mixed infection. Subtyping showed the presence of six different HCV subtypes as follows: 1a (53.2%), 1b (6.4%), 3a (33.0%), 4a (3.2%), and 4d (4.3%). This is the first study describing circulating HCV genotypes among PWID in Tunisia. The distribution of HCV genotypes is distinct from the general population with a predominance of subtypes 1a and 3a. These findings can be used to guide national efforts aiming to optimize the access of PWID to relevant HCV prevention and treatment measures including pangenotypic regimens for patients infected with HCV genotype 3.